EXPERIMENTAL STUDY OF CADMIUM-CITRATE CO-ADSORPTION ONTO α-AL2O3 - Boily J.F.; Fein J.B. (My University, 1996)
An experimental investigation of metal-organic co-adsorption was conducted using cadmium and citrate in the presence of corundum. The experiments were performed in the pH range 3.0 to 10.0 in a 0.01 M NaCl matrix with citrate:Cd ratios of 0.00 and 10.00. The presence of citrate enhances cadmium adsorption between pH 3.5 and 7.2, and reduces it above pH 7.2. The results from the experiments provide constraints on the thermodynamic properties of the surface complexes. We model the adsorption of Cd by quantifying the competition between aqueous CdCit-1 and the surface species, >AlCitCd0, >AlOCd+ and >AlOCdCl0. The experimentally determined equilibrium constants provide a means to predict Cd mobilities in groundwater systems by describing the relative stabilities of surface and aqueous metal-organic complexes as a function of metal-to-ligand and solute-to-sorbent ratios.